PERANCANGAN APLIKASI DIGITAL MENU KAFE COFFE 86 BERBASIS DESKTOP MENGGUNAKAN VISUAL STUDIO 2010 - Givy Devira Ramady; Asep Suherman; Trisha Suci Ramadhanti; Herlina (Prosiding Seminar Nasional Teknoka, 2019)
Technology is developing very fast along with the demands of life and the mobility of human work which continues to increase. Technological advances that have the greatest impact are advances in information technology. the era of information technology opens many business opportunities without having to pay a lot of costs, but has a level of effectiveness and better productivity. The cafe is a place that is usually used as a destination to gather and socialize for all people. Coffe 86 Cafe is one of the cafes that still uses conventional systems in serving its customers. Under these conditions, an implementation of information technology in the form of a digital menu application is expected to minimize ordering errors, shorten order times, and facilitate customers in accessing orders. This digital menu application was developed using Visual Studio 2010 and MySQL as the database. The method used is the waterfall model methodology which is a design method that uses gradual and orderly sequences. With this application, it is expected to help the owner in managing the cafe business to be more developed because this application provides many benefits where every report or transaction can be directly saved into the database.